(untitled) (Journal of Social Sciences Review, 2022)
The present study aimed to assess the role of hemispheric orientation, emotional sensitivity, cognitive imagination and their correlation with the well-being of fine artist students, as well as to evaluate the mediating role of social adaptation. A correlational research design was used, and a sample of 200 artists or people from art communities (100 males and 100 females aged 18 to 30) was selected using purposive sampling. The data collection was done through an open hemispheric brain dominance scale, the Creativity scale created by Kaufman (2012) (K-DOCS), an Emotional sensitivity self-assessment scale, the Mental Health Continuum-short form, and scales for Social adaptation. Data analysis was done through Pearson Product Moment Correlation, Independent Sample t-test, Multiple Regression Analysis, ANOVA and Mediation Analysis test. The results indicated that hemispheric orientation had a statistically significant association with creative imagination, emotional sensitivity, psychological well-being and social adaptation. Moreover, social adaptation significantly mediated the association between hemispheric orientation and creative imagination. The study adds to our understanding of the role of hemispheric orientation, social adaptation and emotional sensitivity in predicting the well-being and creative imagination of artists.